SDSS J075217.84 + 193542.2: X-ray weighing of a secondary BH - Titarchuk, Lev; Seifina, Elena (Frontiers in Astronomy and Space Sciences, 2024)
Precise measurements of black hole (BHs) masses are necessary to understand the coevolution of these sources and their host galaxies. Sometimes in the center of a galaxy there is not one, but two BHs. The BH duality of the quasar nucleus SDSS J075217.84+193542.2 (herein SDSS J0752) was recently proposed based on the observed strict periodicity of optical emission from the source. We tested this assumption using X-ray observations with Swift/XRT (2008)(2009)(2010).We fitted the SDSS J075217 spectrum using a Comptonization model and discovered soft X-ray variability in the 0.3-10 keV energy range. We pursued a scenario in which two supermassive BHs at the center of SDSS J0752 form a pair; and the less massive (secondary) BH periodically crosses/punctures the disk around the more massive (primary) BH. We associate these periodic crossings with tidal disruptions of the disk and, as a consequence, with an increase in X-rays seen as a flare in SDSS J0752. During such an X-ray flare event (2008)(2009)(2010), we discovered a change in the source spectral states and the photon index saturation at the ⇠ 3 level with mass accretion rate Ṁ . For BH mass scaling we used sources: OJ 287, M101 ULX-1 and HLX-1 ESO 243-49, as a reference ones, and found that M SDSS = 9 ⇥ 10 7 solar masses, assuming d SDSS = 500 Mpc. Thus, we obtained a lower limit to a BH mass due the unknown inclination. In addition, we used the virial mass of the secondary BH based on H ↵ -line measurements and we estimated the binary's inclination at SDSS J0752, i = 80 , using a scaling technique.